2017
DOI: 10.1002/sdtp.11895
|View full text |Cite
|
Sign up to set email alerts
|

P‐221L: Late‐News Poster: Indium Gallium Zinc Oxide based Phototransistor for Visible Light Detection by Stacking Solution Processed Defective Oxide Layer

Abstract: Here, we suggest IGZO thin film transistors (TFTs) for detection of visible light region by stacking solution processed defective oxide layer (DOL). DOL was formed at low temperature to intentionally induce higher carbon residues and uncoordinated oxygen species. As a result, IGZO TFTs with DOL showed significantly high detectability under visible light region compared to those without DOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Earlier reports have shown that incomplete annealing of an additional semiconductor film layer can enhance optoelectronic properties of oxide TFTs. 8,11 To confirm that this is not the case with our devices and that the observed improvement in optoelectronic properties can be attributed to inclusion of dye, TFTs were fabricated by the same processing conditions as those with dye/InO x films, but incorporating a film of In 2 O 3 annealed at 250 1C or 300 1C in place of dye/InO x . I/V characteristics presented in Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Earlier reports have shown that incomplete annealing of an additional semiconductor film layer can enhance optoelectronic properties of oxide TFTs. 8,11 To confirm that this is not the case with our devices and that the observed improvement in optoelectronic properties can be attributed to inclusion of dye, TFTs were fabricated by the same processing conditions as those with dye/InO x films, but incorporating a film of In 2 O 3 annealed at 250 1C or 300 1C in place of dye/InO x . I/V characteristics presented in Fig.…”
Section: Resultsmentioning
confidence: 70%
“…8 Therefore, methods are required to enable photosensitization for detection of longer wavelengths. Photoelectric performance of oxide phototransistors can be enhanced by charge carrier engineering, 9,10 for instance, by exploiting metal oxides, 8,[11][12][13][14][15] perovskites, [16][17][18] or quantum dots [19][20][21] for photosensitization. Since first demonstrated in TiO 2 -based photovoltaics, 22 photosensitizing of oxides with small molecule dyes has been broadly studied in dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%